Biomedical Tissue Culture - Ceccherini-Nelli, Luca; Matteoli, Barbara (IntechOpen, 2012)
This book describes many aspects of tissue culture models in an extensive manner. The book includes many topics like, the development of cultural methods to produce massive neuronal syncytial connections and induce their fusion with formation of bi- and multinucleated cells, the applicability in research of cell lines derived from the cultivation of placenta derived cells and cell populations with properties of progenitor/stem cells, the procedures that may be used to regenerate cartilage tissue with appropriate mechanical properties, the improvements made in the use of cell culture for virus isolation, tissue-based models for HCV replication in vitro, cultures to study the pathogenicity of enteropathogenic bacteria, the use of viral DNA and cDNA Array in the diagnosis of respiratory tract infections (RTI) in comparison with routine diagnosis methods.